Ictal pain in focal non-convulsive status epilepticus. Issue 5 (9th June 2017) - Casciato, Sara; Morano, Alessandra; Fattouch, Jinane; Fanella, Martina; Albini, Mariarita; Giallonardo, Anna Teresa; Di Bonaventura, Carlo
Abstract : We report an adult with acute unilateral pain as isolated manifestation of acute symptomatic focal non-convulsive status epilepticus. Pain is rarely a manifestation of epileptic seizures. Traditionally, painful seizures have been thought to originate in either the parietal or temporal lobes, but their localising value is debatable. Recent functional neuroimaging studies and electrophysiological findings obtained by using intracerebral recordings have shown the involvement of the insular cortex along with several other brain structures in the processing of painful inputs, comprising a more widespread anatomo-functional network. Despite their rarity as a distinct clinical entity, especially in adults, painful somatosensory seizures can be disabling and misdiagnosis or delayed diagnosis is common; it is therefore essential to consider epilepsy as a possible cause of paroxysmal pain to ensure proper assessment and appropriate treatment.